Aplicaciones pedagógicas de la balanza digital en procesos de trasformación agroindustrial. - Chanatasig Camalle, Miriam Mercedes (2022)
The present work of integrator project was carried out at the Technical University of Cotopaxi in the career of Agroindustrial Engineering in the Latacunga canton, with the purpose of carrying out the pedagogical applications of the digital scale in agroindustrial transformation processes, for this, the development of an operating manual was carried out, which consists of the technical description, functions, applications, requirements for the proper functioning, whereas the maintenance manual is made up of the different types of maintenance that must be performed when using the balance in the laboratories, in order to support the staff that works in the laboratory in understanding the technical requirements concerning the installation, use, maintenance and recording of the equipment, which is of great relevance for the execution of research activities. The technological and scientific development has incorporated in the equipment several functions and particular modes of operation, which necessarily lead to the implementation of programs to maintain the best operating conditions of the equipment. An experimental design was not used due to the non-existence of points that require a previous analysis; explanatory and descriptive research was used in contemplation of the demonstration of the correct operation and pedagogical application of the scale, a demonstrative practice was carried out, in which chocolate filled with naranjilla marmalade, glycerin-based soap and fruit in syrup was made, taking advantage of the fact that the scale is hugely useful in agribusiness, since it is essential to use accurate weights in the different product processes that are developed.